Synthesis of new pyrazolothiazole derivatives from 4-thiazolidinones - Turgut, Zuhal; Yolacan, Cigdem; Aydogan, Feray; Bagdatli, Emine; Ocal, Nuket (MDPI, 2007)
The synthesis of new 2,3,5,6-aryl substituted tetrahydro-2H-pyrazolo[3,4-d]thiazoles 4a-j as potential biologically active compounds by the cyclocondensation of phenyl hydrazine with new 5-arylidene derivatives 2a-j of 2,3-disubstituted-1,3thiazolidin-4-ones la-e is reported.
Keywords: cyclizations; heterocycles; fused thiazolidines; TRANSFORMATIONS; ALDIMINES; Biochemistry & Molecular Biology; Chemistry